(untitled) - Morgan, Royston Philip Charles (London, 1995)
The book reviews methods used to access the risk of erosion and predict rates of soil loss; outlines the social, economic, political and institutional constraints of soil conservation implementation; presents worldwide coverage of the success and failure in erosion control using international examples; employs reference material from European, African, Australian, American and Asia sources; provides accessible and up-to-date reviews of the mechanics of erosion, erosion models and the art of erosion modelling
Keywords: Soil conservation,Soil erosion